Sumbangan Muhammad Basiuni Imran (m.1974) dalam Pendidikan di Kalimantan Barat, Indonesia: Contribution of Muhammad Basiuni Imran to Education in West Kalimantan, Indonesia - Mohamed, Norahida (Al-Basirah Journal, 2024)
Education is a cornerstone of Islamic civilisation, fostering intellectual and moral development. Throughout history, numerous Islamic scholars have proposed significant ideas to advance education. In the Malay Archipelago, Muhammad Basiuni Imran stands out as a prominent figure who contributed substantially to improving educational quality. Serving as Maharaja Imam during the Sambas Sultanate in West Kalimantan, he initiated numerous reforms in education, which, at the time, took place in teachers’ homes, mosques, and royal palaces. This study examines the background, life, and educational contributions of Muhammad Basiuni Imran, with a particular focus on his thoughts and strategies for educational reform in Sambas, West Kalimantan. Employing a qualitative methodology and content analysis design, the research draws on data from documents, interviews, and observations. Thematic analysis was used to explore his ideas and approaches. The findings reveal that Muhammad Basiuni Imran emphasised essential characteristics for educators and introduced innovative educational models. He established Madrasah Sulthaniyah and Tarbiyatul Islam, institutions that integrated ‘aqli (intellectual) and naqli (revealed) knowledge. Furthermore, he conducted informal religious studies through Majlis Tashwir, fostering community engagement in Sambas. These efforts highlight his key role in the advancement of education in West Kalimantan, Indonesia.